CHANGES IN HIGHER EDUCATION INSTITUTIONS ON THE WAY TO SUSTAINABLE DEVELOPMENTО РОЗВИТКУ - Запухляк, Іванна Богданівна; Verbovska, Lesya; Маланюк, Назарій Ігорович; Бойко, Марина Олександрівна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2023)
The article proves that higher education institutions should be a full-fledged subject of the implementation of the concept and goals of sustainable development, and not just an institution for education about sustainable development. It is substantiated that in recent years there has been an increase in the role of education in the implementation of the Sustainable Development Goals, firstly, from the standpoint of transformation to ensure quality education; secondly, to ensure the scientific component of the implementation of the Sustainable Development Goals; thirdly, to create an environment for the dissemination of knowledge and practices about sustainable development; fourthly, to ensure the transition of participants in educational and scientific processes from carriers of ideas and principles of sustainable development to subjects of sustainable development in society, economy, culture. The necessity of harmonizing the personal and professional goals of students and teachers with environmental sustainability, social equality and economic efficiency is proved. The approaches to understanding the concept of "education for sustainable development" are investigated, which allowed to define education as one of the most important tools for achieving sustainable development through the formation of a new way of thinking and understanding of the deep connections between the economy, energy, environment and social well-being; and through the formation of responsibility and civic engagement in the implementation of sustainable development. The features of "education for sustainable development", principles and spheres of influence are considered, which allowed to outline the role of higher education in the implementation of sustainable development and to identify changes in higher education to achieve the goals of sustainable development. The components of higher education institutions are highlighted, which directly affect the economic growth of the region and the country through the quality of graduates, commercialization of scientific research, formation of cultural dialogue, reduction of the carbon footprint of the university, energy saving management of the educational institution and establishment of cooperation, improve business and society, prevent climate change, and contribute to the establishment of sustainable society and sustainable territorial development. It is proved that the development of higher education institutions, especially technical ones, should harmonize and ensure the interconnections between sectoral economies, energy, environment and social welfare for sustainable development.